A first-principles study of electronic structure and photocatalytic performance of GaN–MX2 (M = Mo, W; X= S, Se) van der Waals heterostructures. Issue 41 (29th June 2020) - Khan, Fawad; Idrees, M.; Nguyen, C.; Ahmad, Iftikhar; Amin, Bin
Abstract : Modeling novel van der Waals (vdW) heterostructures is an emerging field to achieve materials with exciting properties for various devices. Abstract : Modeling novel van der Waals (vdW) heterostructures is an emerging field to achieve materials with exciting properties for various devices. In this paper, we report a theoretical investigation of GaN–MX2 (M = Mo, W; X= S, Se) van der Waals heterostructures by hybrid density functional theory calculations. Our results predicted that GaN–MoS2, GaN–MoSe2, GaN–WS2 and GaN–WSe2 van der Waals heterostructures are energetically stable. Furthermore, we find that GaN–MoS2, GaN–MoSe2 and GaN–WSe2 are direct semiconductors, whereas GaN–WS2 is an indirect band gap semiconductor. Type-II band alignment is observed through PBE, PBE + SOC and HSE calculations in all heterostructures, except GaN–WSe2 having type-I. The photocatalytic behavior of these systems, based on Bader charge analysis, work function and valence and conduction band edge potentials, shows that these heterostructures are energetically favorable for water splitting.